Measuring Fourth-Year Undergraduates’ Behavioral Intention to Use Chaoxing Learning Platform in The Post-Pandemic in Anhui, China - Li, Yuze (Scholar: Human Sciences, 2024)
Purpose: This study investigates the factors that measuring undergraduates’ behavioral intention to use Chaoxing learning platform in the post-pandemic in Anhui which are determined by perceived ease of use, perceived usefulness, attitude, behavior intention, facilitating conditions, self-efficacy and subjective norm. Research design, data, and methodology: The study’s target population comprises 500 fourth-year undergraduate students who have a minimum of one year of experience using the Chaoxing Learning Platform. These students are drawn from three universities in Anhui, China, namely Anhui University of Finance and Economics, Bengbu University, and Tongling University. To assess validity, reliability, model fit, and test hypotheses, the researchers utilized statistical techniques such as Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: The results show that perceived usefulness is significantly impacted by perceived ease of use and facilitating conditions. Behavioral intention is significantly impacted by perceived usefulness, self-efficacy and subjective norm. Attitude is significantly impacted by self-efficacy and subjective norm. There are non-supported relationships between perceived usefulness, perceived ease of use attitude, facilitating conditions and behavioral intention. Conclusions: The recommendations focus on improving user experience, addressing concerns, leveraging social influence, and providing ongoing support, ultimately leading to increased intention and engagement with the platform.